Advances in rectal drug delivery systems. (26th November 2018) - Purohit, Trusha J.; Hanning, Sara M.; Wu, Zimei
Abstract: Drug delivery via the rectum is a useful alternative route of administration to the oral route for patients who cannot swallow. Traditional rectal dosage forms have been historically used for localized treatments including delivery of laxatives, treatment of hemorrhoids and for delivery of antipyretics. However, the recent trend is showing an increase in the development of novel rectal delivery systems to deliver drug directly into the systemic circulation by taking advantage of porto-systemic shunting. The present review is based on research studies carried out between years 1969–2017. Data for this review have been derived from keyword searches using Scopus and Medline databases. Novel rectal drug delivery systems including hollow-type suppositories, thermo-responsive and muco-adhesive liquid suppositories, and nanoparticulate systems incorporated into an appropriate vehicle have offered more control over delivery of drug molecules for local or systemic actions. In addition, various methods for in vitro – in vivo evaluation of rectal drug delivery systems are covered which is as important as the formulation, and must be carried out using appropriate methodology. Continuous research and development in this field of drug delivery may unleash the hidden potential of the rectal drug delivery systems.